Theories about brain/mind system: psychoeducational implications - Lopera Echeverri, Egidio (Pensando Psicología, 2010)
Review of research’s public progress about current theories explaining brain/mind system interaction, expands understanding of learning-teaching process based on shared meaning. Educational Psychology’s study object, theoretical and applied field of transdisciplinary convergence from Cognitive Psychology and Educational Sciences, is the school’s conceptualization as an interpersonal relationships ecosystem, constructed throughout the pedagogical act, understood like a didactic mediation that facilitates through plurality of methods the relation between student’s previous knowledge, and the construction of new explanations about reality. In this interactive scene, where a complex framework of activity and communication the integral development of the student and also his personality as a unitary and articulated set of knowledge, attitudes, emotions, motives and interests is constructed. Through the process of finding meaning and social recognition, students, through their working groups, succeed creating acceptance and affection links with other people, which promotes their self-concept and self-esteem to projec them socially and morally.